Bergenin, Suatu Dihidroisokumarin dari Kayu dan Kulit Batang Shorea Stenoptera Burck§ - Euis Holisotan Hakim; Rudiyansyah Rudiyansyah; Iqbal Musthapa; Koichi Takeya (Institute for Research and Community Services (LPPM) ITB, 2003)
Bergenin, a dihydroisocoumarin derivative of glucopyranosyl gallic acid had been isolated for the first time from ethyl acetate extracts of the heartwood and tree bark, together with (-)-Î±-viniferin from the tree bark of Shorea stenoptera. The structure of bergenin was elucidated based on analysis of spectroscopic data UV, IR, MS, 1H and 13C NMR. Bergenin showed weak cytotoxic activity against murine leukemia P-388 cells (IC50 >100 Î¼g/mL), and also weak toxicity against Artemia salina shrimps (LC50 >500 Î¼g/mL).